Budaya Pendidikan Islam di Kesultanan Buton pada Masa Pemerintahan Sultan Muhammad Idrus Kaimuddin (Abad Ke -19 ) - La Ode Muhammad Syahartijan; La Ode Jumaidin (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This study aimed to analyze the network of Islamic education in the Sultanate of Buton during the reign of Sultan Muhammad K. Kaimuddin. In addition, this study was also aimed to determine the factors that support public acceptance of the teachings application of Islam in the Sultanate of Buton during the reign of Sultan Muhammad K. Kaimuddin. The method used in this study was the historical method with a qualitative approach. Data collections techniques used were interviews, the study documentation through texts, literature study and observation. The results showed that: 1) a network of Islamic education in the Sultanate of Buton on 19th century had implemented an education system that integrates the local culture with the values ​​of the Qur'an based Sufism. The education system had been able to provide the ability for the Sultanate to build a political system, governance and security. Islamic education during the Sultanate still clearly visible on the implementation of the attitudes diversity of Buton society capable in integrating the noble values ​​of local with the noble values ​​of the Qur'an that are universal; 2) learning process that starts from the capital city of the Sultanate (the palace) and then spread to Kadie-Kadie onwards to barata region, which was a small kingdoms that had a structure of government and the community itself, take a long time and the process of distribution was quite long. Keywords: cultural education, Islam, Sultanate, Buton